Grzybowski’s Generalized Eruptive Keratoacanthomas in a Patient with Terminal Kidney Disease—An Unmet Medical Need Equally Ameliorated by Topical Imiquimod Cream and Lapacho Tea Wraps: A Case Report - Havenith, Regina (Dermatol Ther (Heidelb), 2021)
INTRODUCTION: Development of singular keratoacanthoma (KA) is generally considered a benign condition as it has a tendency to regress spontaneously in spite of histological similarity to squamous cell carcinoma. Most KAs undergo excision to rule out differential diagnoses. Several alternative treatment modalities (keratinolytic, ablative, immunomodulating, antiproliferative, or targeted therapy) have been described in the past with varying success, underlining the therapeutic challenges associated with large or multiple lesions. Isomorphic response (Koebner phenomenon) may limit the efficacy of ablative options, and comorbidity may limit the use of systemic treatments. Less aggressive topical immunomodulatory treatment options represent an alternative with varying therapeutic success. CASE REPORT: Here, we describe the clinical course of a 51-year-old male patient with terminal kidney disease who suffered from the rare benign pruritic condition of Grzybowski’s generalized eruptive keratoacanthomas (GEKA) and experienced a significant reduction of lesions and symptoms upon topical therapy with imiquimod 5% cream and lapacho tea dressings alike. CONCLUSIONS: Very little is known about the potential antiinflammatory or antiproliferative effects on the epidermis of the popular phytotherapeutic agent lapacho tea. More studies are warranted considering both the etiology and treatment of GEKA and topical use of phytotherapeutics in dermatology in general. Management of large or multiple KAs remains challenging.